(untitled) (Margalla Papers, 2025)
This research examines Pakistan's water crisis and its impact on national security, highlighting key factors such as population growth, climate change, and inadequate water resource management. The article emphasises the urgent need for thorough qualitative changes and improved infrastructure to guarantee sustainable access to clean water. This research employs a qualitative approach to examine the complex relationship between regional relations and water security, with a focus on Pakistan’s transboundary water challenges. Through securitisation theory, the study aims to analyse how water scarcity is framed as a water security issue, exploring the securitisation process and its implications for national security. Utilizing an explanatory research design and document analysis, this study comprehensively assesses both internal and external water security threats to Pakistan’s national security. Additionally, it highlights the importance of regional cooperation and diplomacy in managing shared water resources. Addressing the water crisis is an environmental concern and a vital national security imperative. A comprehensive strategy encompassing legislative changes, technical advancements, and international collaboration is required to mitigate the threat and protect Pakistan's stability. Bibliography Entry Amjad, Sawaira. 2025. "Pakistan’s Water Crisis and Its National Security Implications." Margalla Papers 29 (1): 135-151.